2017
DOI: 10.3346/jkms.2017.32.8.1360
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Atopic Dermatitis in Adults Are Different according to Onset

Abstract: Few studies of atopic dermatitis (AD) in adult patients have evaluated differences in clinical features of AD according to onset age. We aimed to characterize the clinical features of AD in adult patients according to age of onset. Subjects with AD outpatient visiting the Department of Dermatology at Kangnam Sacred Heart Hospital were recruited for this study. A dermatologist conducted clinical evaluation, a survey of demographics, and onset of AD-associated signs and symptoms for each participant. Total immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
5
32
2
1
Order By: Relevance
“…Also, location of skin lesions might vary according to age of onset [37]. Patients in the ADAPT study had mainly pre-adult onset AD, with a mean age of onset of 13.1 years, comparable to other studies [30,37].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Also, location of skin lesions might vary according to age of onset [37]. Patients in the ADAPT study had mainly pre-adult onset AD, with a mean age of onset of 13.1 years, comparable to other studies [30,37].…”
Section: Discussionsupporting
confidence: 73%
“…Patients with persistent AD (pre-adult onset) show increased disease severity, pruritus intensity and comorbidities (e.g., hypertension), compared to those with adult-onset AD [33]. Also, location of skin lesions might vary according to age of onset [37]. Patients in the ADAPT study had mainly pre-adult onset AD, with a mean age of onset of 13.1 years, comparable to other studies [30,37].…”
Section: Discussionsupporting
confidence: 55%
“…ere was also consensus about differences in the clinical presentation of AD according to the patient's age. Even though many common features exist, there are significant differences between the clinical characteristics of children, adolescents, and adult AD subgroups [38]. Moreover, the lack of standardization of outcome measures for clinical signs of AD, such as clinical signs measured with a physician-assessed instrument and symptoms measured with a patient-assessed instrument or control of flares, hampers comparison among studies [39].…”
Section: Discussionmentioning
confidence: 99%
“…AD diagnoses are continuously on the rise, oscillating between 10% and 20% of the pediatric population. e disease affects 1-10% of adults worldwide, and recent studies have suggested that adult AD is more common than previously thought [3,4]. Although AD is not a life-threatening condition, it poses a significant social, psychological, and economic burden [5].…”
Section: Introductionmentioning
confidence: 99%
“…5 No parece haber diferencia entre la DA de inicio precoz y tardío en cuanto a la historia personal o familiar de atopia 5 o en la manifestación de signos y síntomas como xerosis, queilitis y queratosis pilar, entre otros. 9 En el paciente descrito con presentación cutánea atípica, el antecedente de rinitis atópica y las alteraciones laboratoriales como la sensibilidad a aeroalérgenos y eosinofilia fueron esenciales para el diagnóstico. En general no se utiliza biopsia de piel en la investigación de los eccemas, debido a que no permite distinguir entre las posibles etiologías, 4 sin embargo, en el paciente descrito algunas lesiones en placa tenían aspecto infiltrado y sugerían micosis fungoide, diagnóstico eliminado después del análisis de dos fragmentos de piel.…”
Section: Discussionunclassified